Behavioral Finance in the Digital Era: How Fintech Innovations Influence Investor Decision-Making and Risk Perception - Hasanah, Anisaul; Asri Ady, Deni Riani, (Pascasarjana STIE Amkop Makassar, 2024)
This study examines the influence of financial technology innovations on investor decision-making, risk perception, and behavioral biases within the context of robo-advisors. Employing a quantitative research design, the study utilized rendom sampling to gather data from 150 consumers using robo-advisor platforms. The research employed path analysis to evaluate direct and indirect effects among the variables. The findings reveal that financial technology innovations significantly impact behavioral biases, which in turn affect investor decision-making. The relationship between financial technology innovations and risk perception, mediated by behavioral biases, was positive but not statistically significant. This suggests that while financial technology empowers investors, it can also amplify cognitive biases, potentially leading to impulsive decisions. The study highlights the need for user-friendly fintech interfaces that educate investors about risks and biases. By addressing the psychological dimensions of fintech usage, stakeholders can enhance investor outcomes and promote responsible investing practices. Future research should explore educational interventions to mitigate biases and improve risk perception among users of financial technology platforms. Keywords: Fintech Innovations, Behavioral Biases, Investor Decision-Making, Risk Perception.